1995
DOI: 10.1021/bi00033a032
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cyclic Nucleotide-Dependent Protein Kinase Substrate Specificity by the Use of Peptide Libraries on Cellulose Paper

Abstract: An iterative approach to the a priori determination of the substrate specificity of cAMP- and cGMP-dependent protein kinases (PKA and PKG) by the use of peptide libraries on cellulose paper is described. The starting point of the investigation was an octamer library with the general structure Ac-XXX12XXX, where X represents mixtures of all 20 natural amino acids and 1 and 2 represent individual amino acid residues. The library thus contained all possible 2.56 x 10(10) octamers, divided into 400 sublibraries wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 26 publications
6
82
0
1
Order By: Relevance
“…In the erythrocyte, dematin is phosphorylated by an endogenous kinase similar in size and properties to the catalytic subunit of cyclic AMP-dependent kinase (5). The consensus phosphorylation site specificity of the catalytic subunit of cyclic AMP dependent kinase is RRXSX but varies substantially and is quite similar to the KKASF site that is phosphorylated in dematin headpiece (12). Whereas the role of this phosphorylation in vivo is unknown, phosphorylation of dematin inhibits in vitro Factin bundling but not F-actin binding (1,13).…”
mentioning
confidence: 99%
“…In the erythrocyte, dematin is phosphorylated by an endogenous kinase similar in size and properties to the catalytic subunit of cyclic AMP-dependent kinase (5). The consensus phosphorylation site specificity of the catalytic subunit of cyclic AMP dependent kinase is RRXSX but varies substantially and is quite similar to the KKASF site that is phosphorylated in dematin headpiece (12). Whereas the role of this phosphorylation in vivo is unknown, phosphorylation of dematin inhibits in vitro Factin bundling but not F-actin binding (1,13).…”
mentioning
confidence: 99%
“…These two phenylalanine derivatives are commonly used as photoactivatable residues that allow for the covalent cross-linking between peptide ligands and the target protein (50,51). The substrate peptide TQAKRKKSLAMFLR (W64), in which the serine is the phosphate acceptor site (P0), was derived from a library screen directed to identify highly PKGspecific substrates (11,52). This peptide with a K m of 260 nM and a PKG/PKA specificity index of 19.2 is the most selective and specific synthetic substrate for PKG known today (Table 3).…”
Section: Strategy For Determining Peptide-binding Sites Using Photoacmentioning
confidence: 99%
“…Previous studies with peptide libraries defined optimal amino acid sequences (RKX(S/T), X is any amino acid) for phosphorylation by cGK (25). Although GKAP42 is preferentially phosphorylated by cGK-I in vitro and in vivo, a typical cGK phosphorylation site was not identified in GKAP42.…”
Section: Co-localization Of Cgk-i With Gkap42 In Mammalianmentioning
confidence: 99%
“…WT, wild type. defined optimal amino acid sequences for phosphorylation by cGK (RKX(S/T)) (25). Additionally, Glass and Smith (26) reported that the recognition site specific to cGK requires an arginine on the C-terminal side (underlined) of the phosphorylated residue, X(S/T)RX.…”
Section: Figmentioning
confidence: 99%